Joint bleeding in factor VIII deficient mice causes an acute loss of trabecular bone and calcification of joint soft tissues which is prevented with aggressive factor replacement. (8th April 2014) - Lau, A. G.; Sun, J.; Hannah, W. B.; Livingston, E. W.; Heymann, D.; Bateman, T. A.; Monahan, P. E.
Summary: While chronic degenerative arthropathy is the main morbidity of haemophilia, a very high prevalence of low bone density is also seen in men and boys with haemophilia. This study investigates bone degradation in the knee joint of haemophilic mice resulting from haemarthrosis and the efficacy of aggressive treatment with factor VIII in the period surrounding injury to prevent bone pathology. Skeletally mature factor VIII knock‐out mice were subjected to knee joint haemorrhage induced by puncture of the left knee joint capsule. Mice received either intravenous factor VIII treatment or placebo immediately prior to injury and at hours 4, 24, 48, 72 and 96 after haemorrhage. Mice were killed 2‐weeks after injury and the joint morphology and loss of bone in the proximal tibia was assessed using microCT imaging. Quantitative microCT imaging of the knee joint found acute bone loss at the proximal tibia following injury including loss of trabecular bone volumetric density and bone mineral density, as well as trabecular connectivity density, number and thickness. Unexpectedly, joint injury also resulted in calcification of the joint soft tissues including the tendons, ligaments, menisci and cartilage. Treatment with factor VIII prevented this bone and soft tissue degeneration. Knee joint haemorrhage resulted in acute changes in adjacent bone including loss of bone density and mineralization of joint soft tissues. The rapid calcification and loss of bone has implications for the initiation and progression of osteoarthritic degradation following joint bleeding.